2013
DOI: 10.1063/1.4798460
|View full text |Cite
|
Sign up to set email alerts
|

α-helix to β-hairpin transition of human amylin monomer

Abstract: The human islet amylin polypeptide is produced along with insulin by pancreatic islets. Under some circumstances, amylin can aggregate to form amyloid fibrils, whose presence in pancreatic cells is a common pathological feature of Type II diabetes. A growing body of evidence indicates that small, early stage aggregates of amylin are cytotoxic. A better understanding of the early stages of the amylin aggregation process and, in particular, of the nucleation events leading to fibril growth could help identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 86 publications
6
55
0
Order By: Relevance
“…A large β-strand fraction is also seen for each monomer which corresponds to the β-sheet conformations of hIAPP monomer as described in previous studies. 24,26,27 Large fractions of unassigned structures suggest that the hIAPP dimer can also adopt collapsed and amorphous conformations. Region VII corresponds to the U-shaped conformation that is observed in the mature hIAPP fibril, 17 where the DSSP analysis shows a clear strand-loop-stand feature.…”
Section: A Hiapp Fibrillar Dimermentioning
confidence: 99%
See 2 more Smart Citations
“…A large β-strand fraction is also seen for each monomer which corresponds to the β-sheet conformations of hIAPP monomer as described in previous studies. 24,26,27 Large fractions of unassigned structures suggest that the hIAPP dimer can also adopt collapsed and amorphous conformations. Region VII corresponds to the U-shaped conformation that is observed in the mature hIAPP fibril, 17 where the DSSP analysis shows a clear strand-loop-stand feature.…”
Section: A Hiapp Fibrillar Dimermentioning
confidence: 99%
“…18,[21][22][23][24][25][26][27][28][29] The full-length hIAPP monomer has been shown, both computationally and experimentally, to adopt various conformations, including unstructured coils, α-helices, long β-hairpins, and mixed α-helical and β-sheet conformations. [23][24][25][26][27][28][30][31][32][33][34] The interconversions among some of these conformations have also been characterized using advanced sampling techniques. 26,27 This complex folding behavior of the hIAPP monomer is also reflected in the multiple conformations observed for the mature fibrils, as discussed above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, most of the knowledge of the initial phase of hIAPP self-association is based on theoretical methods. Based on a detailed computational analysis, Singh et al [35] reported that in dilute solution, hIAPP can adopt distinct metastable states such as ␣-helical, ␤-hairpin, or unstructured coil, all of them with comparable free energies (Fig. 2).…”
Section: Amyloidogenic Properties Of Hiapp the Cross-␤ Structurementioning
confidence: 97%
“…It is costored with insulin in the secretory granules from which both are cosecreted through exocytosis in response to ␤-cell secretagogues [20][21][22][23]. The hIAPP/insulin molar ratio in the secretion has been estimated to be 1/100 in healthy individuals and could increase to 1/20 in T2DM [35]. Of note is that in vitro, insulin has an inhibitory effect on hIAPP fibrillogenesis.…”
Section: Amyloidogenic Properties Of Hiapp the Cross-␤ Structurementioning
confidence: 98%